2019
DOI: 10.1038/s41467-019-12724-2
|View full text |Cite
|
Sign up to set email alerts
|

Revealing neural correlates of behavior without behavioral measurements

Abstract: Measuring neuronal tuning curves has been instrumental for many discoveries in neuroscience but requires a priori assumptions regarding the identity of the encoded variables. We applied unsupervised learning to large-scale neuronal recordings in behaving mice from circuits involved in spatial cognition and uncovered a highly-organized internal structure of ensemble activity patterns. This emergent structure allowed defining for each neuron an ‘internal tuning-curve’ that characterizes its activity relative to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
148
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(172 citation statements)
references
References 59 publications
14
148
1
Order By: Relevance
“…This motivated the subsequent quantification of single-cell selectivity to specific behaviours using shuffling analyses as well as statistical modelling with a generalized linear model (GLM). All tests indicated that PPC and M2 were driven strongly by performed behaviours, similar to what has been shown in more stereotypical tasks 27 , but extended here to freely behaving animals. The neural coding of observed behaviour, on the other hand, was below chance levels in both brain areas, even in neurons with strong performance correlates.…”
supporting
confidence: 84%
“…This motivated the subsequent quantification of single-cell selectivity to specific behaviours using shuffling analyses as well as statistical modelling with a generalized linear model (GLM). All tests indicated that PPC and M2 were driven strongly by performed behaviours, similar to what has been shown in more stereotypical tasks 27 , but extended here to freely behaving animals. The neural coding of observed behaviour, on the other hand, was below chance levels in both brain areas, even in neurons with strong performance correlates.…”
supporting
confidence: 84%
“…This raises the question of dimensionality of the HD system during 3D motion. Previous studies 47,48 have used unsupervised approaches to reveal the 1D attractor. We did not attempt to generalize these approaches to 3D because our data is currently restricted to 60°tilt in freely moving animals, and because HD responses are largely attenuated in the rotator.…”
Section: Articlementioning
confidence: 99%
“…To test whether the activity in general was low-dimensional, we furthermore applied PCA directly to the deconvolved and z-scored traces of each session separately (Supplementary Figure S5B-D). Additionally, to estimate whether the activity was confined to a non-linear manifold, we calculated the internal dimensionality (Rubin et al, 2019): for a manifold of (nonlinear) dimension d, we expect the average number of neighbours within a small L2-distance r to be proportional to r d (volume of a hypersphere). To estimate d, for each point in time in each session, we found the 500 other timepoints with most similar activity (L2 distance).…”
Section: Pooled-population Activity Trajectoriesmentioning
confidence: 99%